Asymmetric deterioration of spatial awareness with diminishing levels of alertness in normal children and children with ADHD. - Dobler, V. B.; Anker, S.; Gilmore, J. (Journal of Child Psychology & Psychiatry & Allied Disciplines., 2005)
Background: There is growing literature suggesting that some children diagnosed with attention deficit hyperactivity disorder (ADHD) can show a significant bias in attention away from left space. Here we examine mechanisms that may underpin these effects in both clinical and non-clinical child populations. Unilateral spatial inattention (unilateral neglect) is a commonly reported consequence of stroke in adults. Although for most patients the problem is relatively transient, persistent forms of neglect are almost exclusively associated with right hemisphere lesions. It has been suggested that this chronicity may result from co-existing disruption to right hemisphere dominant systems that mediate alertness. Here we present two studies examining the relationship between sustained attention and left spatial awareness in childhood. Method: In the first, normal children without the ADHD diagnosis were administered a non-spatial test of sustained attention/alertness. Children who performed poorly at this task, relative to their more attentive peers, showed a modest but reliable delay in awareness of left-sided visual information. Furthermore, attention towards the left declined for both groups as a function of time-on-task, suggesting a significant within-subject modulatory effect of alertness on spatial awareness. The second study examines this relationship in children referred to clinical services for attention problems. Irrespective of their final diagnosis, children were divided into two groups according to their performance in sustained attention/alertness tasks. Results: The results suggest that, regardless of the children's clinical diagnosis, diminished sustained attention/alertness levels formed the strongest predictor of relatively delayed awareness of information presented within left visual space. Two children within this group exhibited signs of hitherto undetected spatial neglect as severe as that observed in some brain-injured adults. Conclusions: Clinical and theoretical implications are discussed. Reprinted by permission of the publisher.